Management of causal agents of chilli leaf curl complex through bio-friendly approaches (The Journal of Plant Protection Sciences, 2024)
Chilli leaf curl causes huge crop loss in Sundarban Islands that occurs primarily due to attack of thrips, yellow  mites and white fly followed by invasion of chilli leaf curl virus. An attempt was made to find out the cost effec tive management schedule to minimize the crop loss. Seven treatments were taken up for study including two  chemicals i.e. profenophos and diafenthiuron, three ecofriendly approaches i.e. garlic extract, spirit and alternate  use of garlic with spirit, one predator insect Chrysoperla carnea and untreated control. The lowest population of  thrips, mites and white fly was recorded with application of diafenthiuron at 15 days interval from seedling to early  fruiting stage. Among the ecofriendly options, alternate use of garlic with spirit performed better than their single  repeated use starting from seedling to early fruiting stage at every 15 days interval.
Keywords: Chilli leaf curl; mite; thrips; diafenthiuron; garlic extract